Propuesta de reestructuración para Canales Móviles en DAVIVIENDA a partir de metodologías ágiles (2024)
The objective of this thesis is to provide a practical guide for the implementation of agile methodologies in a financial institution, and help leaders of the organization to understand the benefits and challenges of implementing these methodologies. It is also expected that this thesis will contribute to general knowledge about the implementation of these methodologies in this type of reference organizations in the financial sector, the impact it has on customer satisfaction, on culture organization and the massification of profits and successes, while serving as a point of starting point for future research in this field